رفض الأنا للآخر في لامية العرب للشنفرى، قراءة من منظور حداثي كتاب: "بدايات الأشياء لأدونيس أنموذجا - عنترة, عمير (University of Eloued جامعة الوادي, 2021)
شغلت القصيدة العربية القديمة كنص أدبي تراثي اهتمام النقاد العرب المعاصرين فتناولوها بالدراسة والتحليل وذلك بإسقاط المناهج الغربية الحديثة خاصة بعد رواج فلسفة الحداثة وما بعدها، ولم تبق مستهدفة بالدراسات البلاغية والنحوية والصرفية قصد الكشف عن جمالياتها البلاغية واللغوية فحسب، ولما كانت تحتوي قضايا فكرية وفلسفية تتوافق مع التيارين السابقين مثل قضية الأنا والآخر ومسألة البحث عن الهوية والهوية الثقافية، وهذه مقولات حداثية محظة، أخذت من زوايا مختلفة ومتعددة، لكن هذه القضايا رغم أنها كانت مفهومة لدى القارئ العربي إلا أنها بقيت تحتاج إلى النبش عنها ونفض الغبار عن خفاياها ودراستها بمنظور حداثي وما بعد حداثي، قصد الوصول إلى أبعادها الفلسفية وخلفياتها المعرفية وطرح القضايا الواردة فيها بثوب جديد. ويعد الناقد العربي "أدونيس" من أهم النقاد الذين اهتموا بهذه القضية بتقديمه دراسة في الشعر الجاهلي من منظور حداثي مستعملا آليتي الحفر والتنقيب ليكشف عن أهم مسألة من مسائل الحداثة وما بعدها في النص التراثي العربي وبالتحديد قصيدة لامية العرب للشنفرى، وعليه نهدف من خلال هذه الدراسة تقديم قراءة في مشروع أدونيس مع كتابه"بدايات الأشياء" محاولة للإجابة عن بعض الساؤلات المتمثلة في: ما الجديد الذي قدمه أدونيس من خلال دراسته للامية العرب دراسة حداثية؟ وما أهم القضايا التي طرحها؟ وكيف أثبت أن النص التراثي العربي وما يحتويه من قضايا فكرية وفلسفية ليس قاصرا على مساير ومجاراة الفكر العالمي الغربي؟ summary: The old Arabic poem as a heritage literary text occupied the attention of contemporary Arab critics and addressed it in study and analysis by dropping modern Western approaches, especially after the popularity of the philosophy of modernity and beyond, and did not remain targeted in rhetorical, grammatical and pure studies in order to reveal its rhetorical and linguistic aesthetics Only, since they contain intellectual and philosophical issues that correspond to the previous two currents such as the issue of the ego and the other and the issue of the search for identity and cultural identity, these are modern sayings, taken from different and multiple angles, but these issues, although they were understood by the Arab reader only It still needs to be exhumed and dusted from its mysteries and studied with a modernist and post-modern perspective, in order to reach its philosophical dimensions and cognitive backgrounds and raise the issues contained in it in a new dress. The Arab critic "Adonis" is one of the most important critics who were interested in this issue by presenting a study in ignorant poetry from a modern perspective using drilling and exploration to reveal the most important issues of modernity and beyond in the Arab heritage text, specifically a poem of the Arab illiteracy of the Shanfri, and therefore we aim through this study to provide a reading in the project Adonis with his book "Beginnings of Things" in an attempt to answer some of the questions represented in what is new presented by Adonis through his study of Arab illiteracy a modern study? What are the most important issues he has raised? How did it prove that the Arab heritage text and its intellectual and philosophical issues are not limited to the course of western world thought?
مداخلة. الملتقى الدولي: النص التراثي العربي في منظورات الحداثة وما بعدها، الحدود، التصورات، الإشكالات. كلية الآداب واللغات. جامعة الشهيد حمه لخضر – الوادي
Keywords: النصوص التراثية، الحداثة وما بعد الحداثة، أدونيس، الأنا والآخر، الرفض; heritage texts, modernity and postmodernism, Adonis, ego and the other, rejection